2023
DOI: 10.1038/s41591-023-02232-8
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and lung cancer-associated cachexia in TRACERx

Abstract: Cancer-associated cachexia (CAC) is a major determinant of morbidity and mortality in patients with non-small cell lung cancer (NSCLC). Key features of CAC include alterations in body composition and body weight. Here, we explore the association between body composition and body weight with survival and delineate possible biological processes and mediators that contribute to the development of CAC. Computed tomography-based (CT) body composition analysis of 651 patients in TRACERx suggested that patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…Overall, these findings are consistent with prior reports that strongly associate muscle mass wasting with cancer outcomes . A recent study by the TRACERx consortium also observed that SM loss at follow-up is associated with worse OS in patients with early-stage NSCLC treated with surgery . These unfavorable outcomes were observed in association with poor prognostic syndromes, such as cancer cachexia and muscle wasting, associated with decreases in protein synthesis and increases in protein degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these findings are consistent with prior reports that strongly associate muscle mass wasting with cancer outcomes . A recent study by the TRACERx consortium also observed that SM loss at follow-up is associated with worse OS in patients with early-stage NSCLC treated with surgery . These unfavorable outcomes were observed in association with poor prognostic syndromes, such as cancer cachexia and muscle wasting, associated with decreases in protein synthesis and increases in protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…These unfavorable outcomes were observed in association with poor prognostic syndromes, such as cancer cachexia and muscle wasting, associated with decreases in protein synthesis and increases in protein degradation. The TRACERx study reported that patients with early-stage NSCLC with cancer cachexia by BC profiling exhibit an increased expression of metalloproteinases, providing a possible mechanistic explanation for the processes contributing to tumor-induced SM wasting . These results underscore the importance of monitoring changes in SM mass as a prognostic factor for patients receiving systemic therapy for advanced NSCLC, particularly among male individuals.…”
Section: Discussionmentioning
confidence: 99%
“…There was also considerable variability in the exacerbation frequency per year within the study group, although an overall reduction in exacerbations compared to baseline was noted. Future studies could be improved by including a broader range of COPD traits, such as chronic bronchitis, phlegm production, static and dynamic hyperinflation [ 42 ], and inflammatory and genetic markers, as seen in lung cancer studies, which have been associated with cancer cachexia [ 69 ] and include muscle strength (leg or hand grip) and exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has some limitations, including the relatively small sample size and the type of adipose tissue analyzed (SAT); more comprehensive analyses should be performed also on visceral adipose tissue, known to be implicated in several metabolic alterations [ 1 ]. However, SAT is reliable for this type of investigation in humans [ 33 ], especially for studying metabolic alterations during cancer [ 6 , 7 , 10 ], and is easy to obtain without major complications.…”
Section: Discussionmentioning
confidence: 99%
“…During cancer, several metabolic alterations occur and lead to peripheral tissue abnormalities, mainly represented by muscle and adipose tissue atrophy [ 1 , 2 ]. Importantly, both loss of muscularity and adipose tissue have been shown to significantly impact clinical outcomes among cancer patients [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%